2022
DOI: 10.1088/1741-4326/ac351f
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive neoclassical tearing mode seeding in DIII-D with implications for ITER

Abstract: New studies identify the critical parameters and physics governing disruptive neoclassical tearing mode (NTM) onset. An m/n = 2/1 mode in DIII-D that begins to grow robustly after a seeding event (edge localized mode ELM or sawtooth precursor and crash) causes the mode rotation to drop close to the plasma’s E r = 0 rest frame; this condition opens the stabilizing ion-polarization current ‘gate’ and destabilizes an otherwise marginally stable NTM. Our new experimental and theoretical insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Experimental equilibrium reconstructions are used to model NTM dynamics in realistic conditions relevant to DIII-D, ITER, and future burning plasma tokamaks. Simulations use a kinetic reconstruction of an experimental DIII-D ITER Baseline Scenario (IBS) discharge [29,30]. The reconstruction is of an ELMing H-mode discharge with ITER similar shape, β n ∼ 1.8, and q 95 ∼ 3.4.…”
Section: A Experimental Equilibriummentioning
confidence: 99%
“…Experimental equilibrium reconstructions are used to model NTM dynamics in realistic conditions relevant to DIII-D, ITER, and future burning plasma tokamaks. Simulations use a kinetic reconstruction of an experimental DIII-D ITER Baseline Scenario (IBS) discharge [29,30]. The reconstruction is of an ELMing H-mode discharge with ITER similar shape, β n ∼ 1.8, and q 95 ∼ 3.4.…”
Section: A Experimental Equilibriummentioning
confidence: 99%
“…2018; La Haye et al. 2022) and its database has unusually many examples from which to learn statistically. An important caveat with the underlying database is that magnetics-only equilibrium reconstructions need to be used to get excellent database coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these ideas have been applied in disruption prediction research (Tinguely et al 2019). The DIII-D tokamak has a strong track-record of research on TM stability (La Haye et al 2000;Buttery et al 2008;Turco & Luce 2010;Turco et al 2018;La Haye et al 2022) and its database has unusually many examples from which to learn statistically. An important caveat with the underlying database is that magnetics-only equilibrium reconstructions need to be used to get excellent database coverage.…”
Section: Introductionmentioning
confidence: 99%
“…While tolerable in most present devices, the energy deposited by ELMs on the first wall of a tokamak device is expected to scale with the edge plasma pressure p ped , which could easily lead to melting of the wall material in ITER or other high-pressure, reactor-scale devices [3,4]. In addition to the heat flux problem, recent work has found that large magnetic perturbations induced by ELMs may trigger neoclassical tearing modes that lead to disruptions in tokamak plasmas where the equilibrium condition had otherwise been stable [5,6].…”
Section: Introductionmentioning
confidence: 99%